2020
DOI: 10.1002/tax.12311
|View full text |Cite
|
Sign up to set email alerts
|

“The Old White Lady of Kew Gardens”, Hechtia argentea (Bromeliaceae: Hechtioideae), found her homeland in Mexico

Abstract: Hechtia argentea was described from a cultivated pistillate plant of unknown origin. The type specimen consists of a leaf fragment and a portion of a pistillate inflorescence. Hechtia argentea is part of a group of species with rosettes that bloom laterally, showing variation in dimensions and structure of the inflorescences of both sexes through the different years of flowering. Delimitation of species becomes more complicated where staminate and/or pistillate plants of different species are frequently simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the only biogeographic study carried out for this group, Pech-Cárdenas (2015) identified that the biogeographic provinces with the greatest specific richness of Hechtioideae are the Pacific Lowlands, Sierra Madre del Sur, Veracruz, Balsas Basin, and Mexican Highland provinces. Most species have restricted distribution ranges and high endemism rates (Ramírez-Morillo et al 2018b); accordingly, most of these species have been assessed as under some risk category according to the criteria of the International Union for Conservation of Nature (IUCN) (Pech-Cárdenas 2015, Ramírez-Morillo et al 2016, Ramírez-Morillo et al 2020, Romero-Soler et al 2022.…”
mentioning
confidence: 99%
“…In the only biogeographic study carried out for this group, Pech-Cárdenas (2015) identified that the biogeographic provinces with the greatest specific richness of Hechtioideae are the Pacific Lowlands, Sierra Madre del Sur, Veracruz, Balsas Basin, and Mexican Highland provinces. Most species have restricted distribution ranges and high endemism rates (Ramírez-Morillo et al 2018b); accordingly, most of these species have been assessed as under some risk category according to the criteria of the International Union for Conservation of Nature (IUCN) (Pech-Cárdenas 2015, Ramírez-Morillo et al 2016, Ramírez-Morillo et al 2020, Romero-Soler et al 2022.…”
mentioning
confidence: 99%